2021
DOI: 10.1177/21582440211003093
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Influence of Psychological Capital of Chinese University Teachers Upon Job Thriving: Based on Motivational Work Behavior as an Intermediary Variable

Abstract: With the continuous development of the information process, a series of revolutionary changes are occurring in universities such as knowledge acquisition methods, teaching methods, as well as the relation between teaching and learning, which lead to new and higher requirements for teaching staff. Combining the development requirements of China’s new era, starting from the perspective of capital development in universities, we should discuss the influence of universities teachers’ psychological capital on job t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…As shown in Table 5, the direct effect of IQ on PU was present and significant, and the indirect effect of IQ on PU was 0.058, with a t ‐statistic greater than 1.96. The results of the bootstrap analysis with significant mediating effect show that the 95% confidence interval of the indirect effect did not include 0, indicating that an indirect effect existed (Liu et al, 2021). Therefore, the mediating effect was present in our research model, and its size of 14.6% confirmed that the information quality had a mediating effect in the relationship between informativeness and perceived usefulness.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 5, the direct effect of IQ on PU was present and significant, and the indirect effect of IQ on PU was 0.058, with a t ‐statistic greater than 1.96. The results of the bootstrap analysis with significant mediating effect show that the 95% confidence interval of the indirect effect did not include 0, indicating that an indirect effect existed (Liu et al, 2021). Therefore, the mediating effect was present in our research model, and its size of 14.6% confirmed that the information quality had a mediating effect in the relationship between informativeness and perceived usefulness.…”
Section: Resultsmentioning
confidence: 99%
“…Teacher−student relationship is defined as human interplay that developed in the day‐to‐day interaction and communication between teachers and students (Hughes et al, 2012). For graduate students, it is essentially a supportive development relationship between an experienced tutor and a less experienced but promising graduate student (Camas et al, 2021; Liu et al, 2021; Martin & Collie, 2019; Spilt et al, 2011). Especially in the context of China, which emphasizes that “tutor is the first person in charge of graduate student training” (Huang, 2012), teacher−student relationship usually has a significant influence on the life, study and research activities of Chinese graduate students and is a key factor in determining the quality of graduate students training in China (e.g., Li et al, 2022; Liang et al, 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…It serves as a crucial factor influencing turnover and absenteeism and is recognized as a reliable predictor of a team’s capacity to navigate new challenges and organizational change ( Porter et al, 1974 ; Febrianti and Jufri, 2022 ). Recent research by Chanana (2021) and Liu et al (2021) , focusing on teachers during the COVID-19 pandemic, identified a positive relationship between organizational commitment and job satisfaction. Affective commitment, a key element of organizational commitment, has been highlighted in studies such as Koo et al (2020) .…”
Section: Theoretical Backgroundmentioning
confidence: 99%